3D animation for the raw beginner using Autodesk Maya 2026-02-15T20:47:16+03:00 DEBUG: VuFind\ILS\Driver\Folio: Token taken from global cache: eyJhbGciOiJIUzI1NiJ9.eyJzdWIiO... - King, Roger (Roger Alan) (CRC Press/Taylor & Francis Group, 2019)

(untitled)
"3D Animation for the Raw Beginner Using Maya is an ideal academic textbook as well as a superlative do-it-yourself training manual. When employed as a text, it frees the instructor from the painstaking task of developing step-by-step examples to present Maya's complex interface and basic capabilities. When used for individual study, aspiring animators revel in the book's easy-tofollow, hands-on learning style"--